Development of murine model of allogeneic bone marrow transplantation and graft-versus-host disease - I. S. Moiseev; E. A. Burmina; A. V. Botina; M. O. Popova; A. R. Muslimov; O. G. Smykova; K. V. Lepik; K. V. Melsitova; A. I. Shakirova; I. M. Barkhatov; V. V. Baikov; O. V. Galibin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
Modeling of allogeneic bone marrow transplantation and graft-versus-host disease (GVHD) plays a crucial role in the improvement of transplantation procedures and testing novel immunosuppressive drugs. In this study we evaluated the feasibility of busulfan and cyclophosphamide conditioning with posttransplantation cyclophosphamide (150 mg/kg) in donorrecipient pairs C57Bl/6-Balb/с and Balb/с-C57Bl/6. We observed that Balb/с mice as opposed to C57Bl/6 mice can’t be the recipients because of the unacceptably high acute mortality from acute toxicity of chemotherapeutic drug. Histological studies in the C57Bl/6 recipients revealed acute GVHD in 93 % of animals. All animals had only grade I–II severity of GVHD. This model has the potential for future studies in the field of transplantology, nonetheless a decrease in the intensity of prophylaxis is required to augment the manifestations of GVHD.